SAT-200 Clinical Dilemmas of Adrenal Incidentaloma, Is Change in HU Clinically Significant? - Niaz, Azra (J Endocr Soc, 2020)
Introduction There has been a recent increase in the incidence of adrenal incidentaloma (AI), defined as an adrenal mass that’s unintentionally discovered on imaging obtained for an indication other than suspected adrenal pathology, mainly because of increased availability and improved quality of imaging modalities. Differentiation based on malignant vs benign and secretory vs non secretory becomes the most important question on finding such mass. Another important question is long term follow up of these AI. We present a case that highlights the importance of follow up due to the potential of AI to increase in size and density over 3 year. Case A 58 years old male with a history of ESRD secondary to hypertension, controlled hypertension, CAD s/p CABG was seen for a right 1.9 cm AI (found in 11/2016 on noncontrast CT abdomen) with low attenuation of approximately 10 Hounsfield units (HU). He was asymptomatic, normal vitals, and an unremarkable physical exam. Hormonal work up was negative for hyperaldosteronism and Cushing syndrome. About 1 year later, repeat CT abdomen reported an unchanged right, 2.0 x 1.7 cm adrenal mass, 22 HU. Hormonal work-up was not completed and patient was lost to follow up. Two years later, repeat CT abdomen reported increase size of AI to 2.7 cm and increase in attenuation of 24 HU precontract which increased to 55 HU on the immediate postcontrast exam and 55 HU on 13-minute delayed images. Hormonal work up was negative for Cushing syndrome and hyperaldosteronism. Plasma metanephrine was 0.50 with elevated plasma normetanephrine of 3.85. In light of being a renal transplant patient and due to increase in size, change in HU, and significantly elevated normetanephrine levels patient was referred for right adrenalectomy. Discussion Change in adrenal mass size is known to be a significant predictor of malignant potential. An unenhanced attenuation value <10 HU is characteristic of a lipid-rich adenoma, can predict benign adrenal adenoma with 98% specificity, and has a very low likelihood of a pheochromocytoma. European Society of Endocrinology recommends if the AI is homogenous, < 4 cm, with a density ≤ 10 UH, no imaging follow up is recommended and biochemical testing for ruling out pheochromocytoma is indicated in adrenal tumors with an unenhanced attenuation value >10HU. However, the AACE/AAES guidelines recommends AI ≥ 1cm and less than 4cm, repeat imaging with noncontrast CT should be performed at 3–6 months and annually for 1-2 years and if the mass grows or becomes hormonally active then adrenalectomy should be performed. Conclusion There are no prospective studies of the optimal frequency and duration of follow up for AI. Considering the increasing incidence of AI, further studies on the clinical significance of change in HU, such as risk of developing pheochromocytoma, along with standardized international guidelines would be helpful for clinicians in managing patients with AI.